Isolation and Identification of Lactic Acid Bacteria from Raw and Fermented Products and their Antibacterial Activity - D. Selvakumar1*, J. H. Jagannath1, Mallesha1,2, R. Shylaja1,2 (Recent Research in Science and Technology, 2010)
Lactic acid bacteria (LAB) were isolated from raw and fermented products like milk, curd, idli batter and pickle. Out of 44 isolates, 16 species were identified. Among them Enterococcus faecalis was the dominant species (37.5%). Streptococcus pyogenes, Lactobacillus casei and Streptococcus viridans accounted for 18.75%, 18.75% and 6.25% respectively. The remaining 18.75% isolates of Lactobacilli were found to be Leuconostoc sp. Bacteriocin like inhibitory substance (BLIS) from the four isolates except Leuconostoc sp. were tested against selected pathogens of both gram positive and gram negative group. BLIS of E. faecalis in combination with 0.1% Ethylene diamine tetra acetic acid disodium salt (EDTA) showed the best antibacterial activity among all the isolates tested.